Multiple Roles of Green Space in the Resilience, Sustainability and Equity of Aotearoa New Zealand’s Cities - Blaschke, P; Pedersen Zari, M; Chapman, R; Randal, E; Perry, M; Howden-Chapman, P; Gyde, E (MDPI AG, 2024)
Green space is needed in urban areas to increase resilience to climate change and other shocks, as well as for human health and wellbeing. Urban green space (UGS) is increasingly considered as green infrastructure and highly complementary to engineered urban infrastructure, such as water and transport networks. The needs for resilient, sustainable and equitable future wellbeing require strategic planning, designing and upgrading of UGS, especially in areas where it has been underprovided. We explore the implications of these needs for urban development through a detailed review of cited UGS analyses conducted on the larger cities in Aotearoa New Zealand (AoNZ). There are important differences in UGS availability (i.e., quantity), accessibility and quality within and between cities. Some of these differences stem from ad hoc patterns of development, as well as topography. They contribute to apparently growing inequities in the availability and accessibility of UGS. Broader health and wellbeing considerations, encompassing Indigenous and community values, should be at the heart of UGS design and decisionmaking. Most of AoNZ’s cities aim (at least to some extent) at densification and decarbonisation to accommodate a growing population without costly sprawl; however, to date, sprawl continues. Our findings indicate a clear need for the design and provision of high-quality, well-integrated UGS within and servicing areas of denser housing, which are typically areas in cities with a demonstrable UGS deficiency.
Keywords: 33 Built Environment and Design; 3301 Architecture; 3304 Urban and Regional Planning; Clinical Research; Health Disparities; 3.2 Interventions to alter physical and biological environmental risks; 11 Sustainable Cities and Communities; 0502 Environmental Science and Management; 3301 Architecture; 3304 Urban and regional planning; 4104 Environmental management